THE USE OF TEAM GAME TOURNAMENT (TGT) TO IMPROVE STUDENTS’ READING SKILL IN NARRATIVE TEXT ON THE FIRST GRADE AT SMA N 4 PEKANBARU - Wardani, Floris Wardani Floris; Delfi, Syofia Delfi Syofia; ', Syafri K Syafri K (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research was intended to know whether the use of Team Game Tournament (TGT) can improve students’ reading skill in narrative text on the first grade at SMA N 4 Pekanbaru. Besides, this research was also aimed to identify the factors that could improve student’s reading skill through narrative text. To collect the quantitative data, the writer used a test consisted of 40 multiple questions in pre-test, post-test I, and post-test II and qualitative data asking the collaborator to fill the observation sheet and field notes. It was proven by the average score of pre-test was 63.05. then in post-test I, it improved to 71.11 and incredibly improved to 80.06 in post-test II. The factors which cause the improvement are as follows: (!) it can improve their high motivation in learning reading; (2) the students used to have higher competition because they had to compete each other in the tournament to answer the questions;(3) the students could have a chance to help the member of the group who didn’t understand about the material. Based on the finding, it was concluded that the use of Team Game Tournament (TGT) can improve students’ reading skill.Keywords: Team Game Tournament, reading skill, narrative text